2021
DOI: 10.1002/aenm.202100683
|View full text |Cite
|
Sign up to set email alerts
|

An Oxygenophilic Atomic Dispersed FeNC Catalyst for Lean‐Oxygen Seawater Batteries

Abstract: A constant energy supply is crucial for the exploration of deep‐sea extreme environments, and a self‐powered energy conversion device is ideal for this situation. Dissolved‐oxygen seawater batteries (SWBs) that generate electricity by reducing the dissolved oxygen are promising candidates but the ultralow oxygen concentration in deep sea limits the reaction kinetics. As a result, oxygenophilic electrocatalysts for lean‐oxygen conditions are urgently needed. A microwave heating method is reported that achieves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Owing to the incorporation of Ni atoms, the heterointerface results in an optimized effect on the reshaping of the electronic structure of the electrode materials, suggesting a more conductive characteristic of the K 2 Se/Co(Ni 10%). [ 40 ] The calculated DOS analysis and corresponding charge density difference of the K 2 Se/Co(Ni 50%) interface are shown in Figure S24 in the Supporting Information. Conclusively, the controllable electronic engineering not only facilitates the potassium intercalation, but also drives the conversion reaction during the electrochemical process, ultimately leading to an enhancement in the K + storage capacity.…”
Section: Resultsmentioning
confidence: 99%
“…Owing to the incorporation of Ni atoms, the heterointerface results in an optimized effect on the reshaping of the electronic structure of the electrode materials, suggesting a more conductive characteristic of the K 2 Se/Co(Ni 10%). [ 40 ] The calculated DOS analysis and corresponding charge density difference of the K 2 Se/Co(Ni 50%) interface are shown in Figure S24 in the Supporting Information. Conclusively, the controllable electronic engineering not only facilitates the potassium intercalation, but also drives the conversion reaction during the electrochemical process, ultimately leading to an enhancement in the K + storage capacity.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, using this functional ligand in the electrolyte improves the cycling performance at high areal capacities because it inhibits corrosion and dendrite growth. Even in a harsh electrolyte, such as a seawater-based ZnSO 4 electrolyte (Table S2, Figures S50 and S51, Supporting Information), [53] the EDTA-Zn complex still gives the full cell remarkable corrosion resistance and reversibility. Hence, the high stability of the Zn anode with the EDTA-based electrolyte has been proved to give a better performance in full cells in not only a traditional electrolyte but in seawater.…”
Section: Building a Long-life Zn-ion Batterymentioning
confidence: 99%
“…29,30 In recent years, many catalysts with M-N 4 active sites in a symmetric coordination environment have been reported. [31][32][33][34] However, with the deepening of the research, researchers found that compared with the relatively traditional M-N 4 symmetric structure, the coordination environment and electronic structure of the catalyst can be exibly designed through a reasonable adjustment of the asymmetric coordination structure. Asymmetric coordination approach brings satisfactory catalytic performance to M-N-C catalysts.…”
Section: Introductionmentioning
confidence: 99%